Intranasal IL-4 Administration Alleviates Functional Deficits of Periventricular Leukomalacia in Neonatal Mice - Yu, Lin-chao; Miao, Jing-kun; Li, Wei-bin; Chen, Na; Chen, Qi-xiong (Frontiers in Neurology, 2020)
Background: Periventricular leukomalacia (PVL) is the major form of brain injury in premature infants. Currently, there are no therapies to treat PVL. Several studies suggested that polarization of microglia, a resident macrophage-like immune cell in the central nervous system, plays a vital role in brain injury and recovery. As an important mediator of immunity, interleukin-4 (IL-4) has critical effects on many immune cells, such as astrocytes and microglia. Increasing evidence shows that IL-4 plays a well-established role in attenuating inflammation in neurological disorders. Additionally, as a noninvasive and highly effective method, intranasal drug administration is gaining increasing attention. Therefore, in our study, we hypothesized that intranasal IL-4 administration is a promising strategy for PVL treatment. Methods: The therapeutic effects of IL-4 on neuroprotection were evaluated using a Control group, Hypoxia group, and Hypoxia + IL-4 treatment group. The PVL mouse model was established by a severe acute hypoxia (SAH) protocol. Exogenous IL-4 was intranasally administered to investigate its neuroprotective effects. A functional study was used to investigate neurological deficits, immunohistochemical technology and Western blotting were used to detect protein levels, and electron microscopy was used to evaluate myelination. Results: The results suggested that hypoxia stimulated Iba1+ microglial activation, downregulated myelin-related gene (NG2, MAG, and MBP) expression, reduced MBP protein levels, and caused neurological deficits. However, the intranasal administration of exogenous IL-4 partially inhibited Iba1+ microglial activation, improved myelination, and alleviated neurological deficits. The mechanistic study showed that IL-4 improved myelination possibly through the IL-4Ra-mediated polarization of microglia from the M1 phenotype to the M2 phenotype. Conclusion: In summary, our findings demonstrated that the intranasal administration of exogenous IL-4 improves myelination and attenuates functional deficits in a hypoxia-induced PVL model. Intranasal IL-4 administration may be a promising strategy for PVL treatment, for which further mechanistic studies are urgent.